The Administration Staff Appraisal Level of the Organizational Context at Ajlun University College - Omar A. Rababah (Sultan Qaboos University, 2013)
This study aims to test the organizational atmosphere from the staff perspective at Ajlun University College. Specifically, the study raises few questions: What are the dimensions of the organizational atmosphere at the university according to the educational administrative literature? What is the reality of the organizational atmosphere at Ajlun University College, Al Balqa Applied University? What is the operational proposal of developing the organization atmosphere at Ajlun University College? The researcher administered a twenty-four-item instrument to 95 members of the administration staff of the college. The major dimensions of the university organization were found to be: decision-making, social relationships, the organizational belonging, and the organizational atmosphere.The study revealed that the level of the organizational atmosphere was average.To improve the organizational atmosphere, the study recommends that meetings be arranged to bring together both the administration and the staff to discuss their problems, listen to their opinions and suggestions and enhance the financial and moral incentives through allocating proper budgets. The study also recommends conducting studies to identify the causes of the low level of effectiveness of some of the organizational dimensions.